PENGARUH PENDAPATAN ORANGTUA TERHADAP MOTIVASI ANAK-ANAK SMP DESA PULAU LIMBUNG UNTUK MELANJUTKAN PENDIDIKAN - Masita, Masita; Bahari, Yohanes; Zakso, Amrazi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title of this research is "The Influence of Parent Income on Motivation of Junior High School Children of Pulau Limbung Village to Continue Education". This study aims to determine the general problems in this study, namely "How to Influence Parents' Income on the Motivation of Children to Continue Education". With sub-problems: (1) How big is the influence of parental income on the motivation of Limbung Island junior high school children (2) How is the motivation of children to continue education. The form of research used in this study is quantitative research with descriptive research methods and forms of correlation studies with the number of respondents 83 people. Data collection techniques used indirect techniques using questionnaires or questionnaires and documentation techniques in the form of archives or records relating to parental income and motivation of children to continue their education. While data management techniques and data analysis using Simple Linear Regression analysis with the help of SPSS 18. the results of the study prove that 1. the influence of parents' income on the motivation of children in SMP Limbung Middle School to continue their education is 25 categorized as low. 2. the motivation of children to continue their education is very high at 93%. Adjusted R Square determinant value = 0.25 which means the influence of motivational parent income for SMP Limbung Island children is categorized as low at25%.Keywords: Income, Motivation, Education.